Critical role of fractalkine (CX3CL1) in cigarette smoke-induced mononuclear cell adhesion to the arterial endothelium. Issue 2 (9th November 2012) - Rius, Cristina; Company, Chantal; Piqueras, Laura; Cerdá-Nicolás, Jose Miguel; González, Cruz; Servera, Emilio; Ludwig, Andreas; Morcillo, Esteban J; Sanz, Maria-Jesus
Abstract : Background: Cigarette smoking is an important risk factor for the development of cardiovascular disease, yet the pathways through which this may operate are poorly understood. Therefore, the mechanism underlying cigarette smoke (CS)-induced arterial endothelial dysfunction and the potential link with fractalkine/CX3 CL1 upregulation were investigated. Methods and results: Stimulation of human arterial umbilical endothelial cells (HUAECs) with pathophysiological concentrations of CS extract (1% CSE) increased CX3 CL1 expression. Neutralisation of CX3 CL1 activity under dynamic flow conditions significantly inhibited CSE-induced mononuclear cell adhesion to HUAECs (67%). The use of small interfering RNA (siRNA) revealed that nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 5 (Nox5) but not Nox2 or Nox4 is the main NADPH isoform involved in CSE-induced CX3 CL1 upregulation and mononuclear cell arrest. Knock down of HUAEC tumour necrosis factor α expression with siRNA or pharmacological inhibition of p38 mitogen-activated protein kinase and nuclear factor κB also abolished these responses. Interestingly, circulating monocytes and lymphocytes from patients with chronic obstructive pulmonary disease (COPD) (n=29) versus age-matched controls (n=23) showed CX3 CR1overexpression. Furthermore, CX3 CL1 neutralisation dramatically diminished their enhanced adhesiveness to CSE-stimulated HUAECs. Finally, when animals were exposed for 3 days to CS, a mild inflammatory response in the lung was observed which was accompanied by enhanced CX3 CL1 expression in the cremasteric arterioles, an organ distant from the lung. CS exposure resulted in increased leukocyte–arteriolar endothelial cell adhesion which was significantly reduced (51%) in animals lacking CX3 CL1 receptor (CX3 CR1). Conclusions: These results suggest that CS induces functional CX3 CL1 expression in arterial endothelium and leukocytes from patients with COPD show increased CX3 CL1-dependent adhesiveness. Therefore, targeting the CX3 CL1/CX3 CR1 axis might prevent COPD-associated cardiovascular disorders.